Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1101/449330
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptional dynamics following freezing stress reveal selection for mechanisms of freeze tolerance at the poleward range margin in the cold water intertidal barnacleSemibalanus balanoides

Abstract: Transcriptional dynamics following freezing stress reveal selection for mechanisms of freeze 3 tolerance at the poleward range margin in the cold water intertidal barnacle Semibalanus 4 balanoides 5 6 Running title: Transcription following freezing in S. balanoides 7 Abstract 22The ability to survive freezing has repeatedly evolved across multiple phyla. This suggests that 23 the mechanisms of freeze tolerance must be readily evolvable from basal physiological traits. 24While several biochemical correlates to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 77 publications
(101 reference statements)
0
9
0
Order By: Relevance
“…Arctic populations of Fucus spp. can survive extended exposure to sub‐zero air temperatures without injury (Parker 1960, Becker et al 2009), and M. edulis and S. balanoides can survive air temperatures below −10°C (Thyrring et al 2015b, Marshall et al 2018). Thus, local environmental conditions on scales relevant to the organisms do not induce any vertical changes in the presence of foundation species in north Greenland.…”
Section: Discussionmentioning
confidence: 99%
“…Arctic populations of Fucus spp. can survive extended exposure to sub‐zero air temperatures without injury (Parker 1960, Becker et al 2009), and M. edulis and S. balanoides can survive air temperatures below −10°C (Thyrring et al 2015b, Marshall et al 2018). Thus, local environmental conditions on scales relevant to the organisms do not induce any vertical changes in the presence of foundation species in north Greenland.…”
Section: Discussionmentioning
confidence: 99%
“…across the intertidal assemblage, have a strong recovery capacity as they are able to reproduce, grow and recolonize following physical disturbance by ice (Kiirikki & Ruuskanen, 1996; Ørberg et al, 2018). Moreover, recent studies have shown adaptation to local environmental conditions takes place in intertidal Arctic populations of barnacles ( S. balanoides ) (Marshall et al, 2018) and blue mussels ( M. edulis ) (Telesca et al, 2019; Thyrring et al, 2020a). Thus, West Greenland’s intertidal ecosystem seems resilient to gradual climate change, and it is likely that introduced species could pose a greater risk for intertidal assemblages than climate change as increased shipping and propagule transport with the Irminger current increase the potential for introduction of non-native species (Ingolfsson, 1992; Renaud et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…across the intertidal assemblage, have a strong recovery capacity as they are able to reproduce, grow and recolonize following physical disturbance by ice (Kiirikki & Ruuskanen, 1996;Ørberg et al, 2018). Moreover, recent studies have shown adaptation to local environmental conditions takes place in intertidal Arctic populations of barnacles (S. balanoides) (Marshall et al, 2018) and blue mussels (M. edulis) (Telesca et al, 2019;Thyrring et al, 2020a).…”
Section: A Resilient Ecosystemmentioning
confidence: 99%
“…For instance, having evolved in a constant cold environment, Antarctic benthos is highly stenothermal with a small thermal window and a poor capacity to acclimate to elevated temperatures (Peck et al ., 2014). In temperate species, thermal adaptation involves change in enzymatic activity and gene expression, resulting in a reduced upper thermal tolerance in high latitude populations (Sokolova and Pörtner, 2001; King et al ., 2018; Marshall et al ., 2018). Our study demonstrates a different response in M. edulis .…”
Section: Discussionmentioning
confidence: 99%
“…For example, increased haemolymph concentrations of calcium and taurine have together with anaerobic byproducts, such as strombine, been shown to protect membranes and increase freeze tolerance of intertidal bivalves (Murphy, 1977; Loomis et al ., 1988). Furthermore, polar organisms often have additional heat shock proteins (HSP) (Peck, 2016), and the HSP production is upregulated in cold-adapted populations of intertidal barnacles ( Semibalanus balanoides ) following exposure to low air temperatures (Marshall et al ., 2018). The role of HSP in freeze tolerance is poorly understood, yet these chaperones may protects cells from freeze induced cell destabilization and irreversible protein denaturation, and should be investigated further.…”
Section: Discussionmentioning
confidence: 99%